The content of general practice consultations: cross-sectional study based on video recordings - Salisbury, Chris; Procter, Sunita; Stewart, Kate; Bowen, Leah; Purdy, Sarah; Ridd, Matthew; Valderas, Jose; Blakeman, Tom; Reeves, David (British journal of general practice, 2013)
Demographic and policy changes appear to be increasing the complexity of consultations in general practice. To describe the number and types of problems discussed in general practice consultations, differences between problems raised by patients or doctors, and between problems discussed and recorded in medical records. Cross-sectional study based on video recordings of consultations in 22 general practices in Bristol and North Somerset. Consultations were examined between 30 representative GPs and adults making a pre-booked day-time appointment. The main outcome measures were number and types of problems and issues discussed; who raised each problem/issue; consultation duration; whether problems were recorded and coded. Of 318 eligible patients, 229 (72.0%) participated. On average, 2.5 (95% CI = 2.3 to 2.6) problems were discussed in each consultation, with 41% of consultations involving at least three problems. Seventy-two per cent (165/229) of consultations included problems in multiple disease areas. Mean consultation duration was 11.9 minutes (95% CI = 11.2 to 12.6). Most problems discussed were raised by patients, but 43% (99/229) of consultations included problems raised by doctors. Consultation duration increased by 2 minutes per additional problem. Of 562 problems discussed, 81% (n = 455) were recorded in notes, but only 37% (n = 206) were Read Coded. Consultations in general practice are complex encounters, dealing with multiple problems across a wide range of disease areas in a short time. Additional problems are dealt with very briefly. GPs, like patients, bring an agenda to consultations. There is systematic bias in the types of problems coded in electronic medical records databases.